The role relationship capital as the mediator between trade union and work environment / Dg Kamisah Ag Budin … [et al.] - Ag Budin, Dg Kamisah; Stephen, Jacqueline Koh Siew Len; Mohd Salleh, Noorziah; Rosline @ Ruslim, Abdul Kadir (Institute of Research Management and Innovation (IRMI), 2016)
Globally, we are witnessing the weak trade union movement particularly in developing countries. The weak trade unions for instance reflect deficiencies of trade union in improving the employees' terms and conditions employment (Chen and Chan 2004; Freeman 2004; Fossum 2006; Mohamed, Shamsudin et al. 2010). In other words, weak trade unions are associated to the lack of relationship capital and poor outcomes of collective bargaining between trade union leaders and management (Lee, 2009. Weak trade unions cause poor collective bargaining outcomes such as poor working environment. In fact, trade unions in Malaysia was facing a similar problem whereby Malaysia's trade unions is weak and affect the trade unions competencies in improving the employees' welfare as well working environment (Ariffin 1997; Mohamed, Shamsudin et al. 2010)…